RELEVANCY OF CORPORATE GOVERNANCE DURING FINANCIAL - 1. Dr. Karan Singh Gaur, 2. Garima Yadav, 3. Janvi Sharma (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Corporate governance is a fundamental part of governance in the corporate world. There are cluster of principles that can be applied to any organization's governance. This article offers a review of the condition of governance in corporate and delves, into the significant factors that have played a role in the ongoing financial crisis. Corporate governance is a process encompassing aspects with particular importance placed on its role, in the United States. The Anglo-American Model is being premised to increase the value of shareholders. This model is developed with free market economy and assumption of separating ownership and control is held in the corporation. It sensitizes corporate leaders for the importance of good Corporate Governance. Its importance as technology has changed organization in a dynamic manner and created new business opportunities. Companies are increasingly interested in companies that prioritize environmental, social, and governance (ESG) practices, and shareholder engagement has evolved into an important instrument for ESG engagement. Good corporate governance plays a role, in fostering the growth of capital markets in underdeveloped countries. It has been observed that a weak corporate governance structure not hampers performance but also exposes the entire financial system to vulnerabilities. In India, corporate governance is an evolving process, as it is around the world. The literature on corporate governance continues to produce a plethora of factors with complex, poorly understood interrelationships. The Indian corporate governance system will be able to evolve in a more organized manner with the notification of literature on “Governance in Companies” built on multiple models; the research of global trends in relation to this system; and the structuring of the system based upon the observations made.